2015
DOI: 10.1177/1535370214565078
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Deficiency of G-protein coupled receptor 40, a lipid-activated receptor, heightens in vitro- and in vivo-induced murine osteoarthritis

Abstract: Osteoarthritis (OA) is an age-related degenerative joint disease. To date, its management is focused on symptoms (pain and inflammation). Studies suggest that fatty acids can reduce the expression of inflammatory and catalytic mediators, and improve in vivo joint function. Free fatty acid receptors (FFARs) such as G-protein coupled receptor 40 (GPR40) are proposed as attractive therapeutic targets to counteract inflammation and cartilage degradation observed in OA. This study aims to elucidate the involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Furthermore, Gpr40 downregulation protects osteocytes from apoptosis. 374 Wauquier et al 43 observed that Gpr40 −/− mice had a reduction in BMD and bone mass with higher promoting osteoclast differentiation, and Monfoulet et al 375 observed a more severe OA-induced phenotype in Gpr40 −/− mice, marked by elevated tidemark exposure, osteophyte formation, and subchondral bone sclerosis (Table 9).…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
“…Furthermore, Gpr40 downregulation protects osteocytes from apoptosis. 374 Wauquier et al 43 observed that Gpr40 −/− mice had a reduction in BMD and bone mass with higher promoting osteoclast differentiation, and Monfoulet et al 375 observed a more severe OA-induced phenotype in Gpr40 −/− mice, marked by elevated tidemark exposure, osteophyte formation, and subchondral bone sclerosis (Table 9).…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 99%
“…Chondrocytes express membrane receptors both for FAs and lipoproteins, including GPR40 and GPR120, TLR4, and CD36, as well as some members of the LDLR and LRP families . Global knockout of GPR40 has been shown to increase predisposition to injury‐induced OA in a mouse model and, when challenged with interleukin 1 beta (IL‐1β), the GPR40 −/− chondrocyte produced more inflammatory molecules, such as IL‐6, PGE 2 , MMP‐2, and MMP‐9, compared with wild‐type cells . Interestingly, Dehne and coworkers reported that GPR40 is upregulated in human OA chondrocytes .…”
Section: Cartilage and Fatty Acidsmentioning
confidence: 99%
“…Recently, we demonstrated in vivo and in vitro the implication of this receptor in bone homeostasis . GPR40 −/− mice were characterized by an osteopenic/osteoporotic phenotype when compared to wild‐type (WT) littermates.…”
Section: Introductionmentioning
confidence: 99%